A Scalable Chemical Approach for the Synthesis of a Highly Tolerant and Efficient Oil Absorbent. Issue 24 (15th October 2019) - Shome, Arpita; Maji, Kousik; Rather, Adil Majeed; Yashwanth, Arcot; Patel, Deepak Kumar; Manna, Uttam
Abstract: In the past, bio‐inspired extreme water repellent property has been strategically embedded on commercially available sponges for developing selective oil absorbents. However, most of the reported materials lack physical and chemical durability, limiting their applicability at practically harsh settings. Herein, a stable dispersion of polymeric nanocomplexes was exploited to achieve a chemically reactive coating on the highly compressible melamine foam. A superhydrophobic melamine foam (SMF) was achieved after post‐covalent modification of the reactive coating through 1, 4‐conjugate addition reaction at ambient conditions. The durability of the embedded extreme water repellent property in the as‐modified melamine foam has been elaborately demonstrated through exposing it to severe physical manipulations, chemically harsh aqueous media including pH 1, pH 12, surfactant contaminated water, river water, seawater and prolonged UV irradiation. Thus, the highly tolerant SMF was utilized as an efficient oil absorbent wherein oils of varying densities could be selectively recovered from an oil/water interface with high (e.g., 137 g g −1 for chloroform and 83 g g −1 for diesel) oil absorption capacity. Moreover, the selective oil absorption capacity of the as‐synthesized material remained unaffected at practically relevant severe chemical and physical settings, and the extreme water repellency of the material remained unaltered even after repetitive (at least 50 cycles) use for oil/water separation. Abstract : A facile and scalable chemical approach is adopted to develop a highly tolerant oil absorbent that is capable of performing at severe settings. The strategic use of a chemically reactive nanocomplex allowed to develop an amine‐reactive and covalently cross‐linked polymeric coating on melamine foam, which displayed robust superhydrophobicity after post‐covalent modification with a selected alkylamine. The synthesized superhydrophobic sponge selectively and rapidly absorbed an oil and water‐immiscible organic solvent with a maximum absorption capacity of 137 g g −1 and remained efficient to perform repetitively.